Moderating Effect Of Executive Characteristics In The Effect Of Transfer Pricing On Tax Avoidance - Verna Budi Amanda; Verani Carolina (Universitas Muhammadiyah Malang, 2021)
Tax avoidance is commonly considered as an act which can make a country suffering a great loss. Transfer pricing scheme is one of the most common activity that usually multinational enterprises do regarding to the tax avoidance. The aims of this research are to test and find an emphirical evidence regarding to the effect of transfer pricing on tax avoidance and the effect of transfer pricing on tax avoidance with executive characteristics as a moderate variable. The population of this research is all of the manufacturing companies that are listed in Indonesia Stock Exchange (IDX) during the years of 2017-2019. This research sample is determined by the purposive sampling technique. The method of analysis used in this research is regression analysis method. The results shows that transfer pricing has an effect to tax avoidance and executive characteristic can positively moderate the effect of transfer pricing on tax avoidance.